Aging and the eye - (:unkn) unknown (My University, 2005)
Aging is a fundamental biologic phenomenon that occurs even in the absence of disease, each cell having a genetically programmed lifespan. Tissues that do not undergo mitotic division to replace this cell fallout, such as the central nervous system and the retina, have a high incidence of aging manifestations, particularly after 75 years of age. As the lens ages, it increases in weight and thickness and decreases in accommodative power. No method to halt the formation of age-related macular degeneration and/or senile cataract has been shown to be effective. Nevertheless, advances in the treatment of age-related macular degeneration and advances in surgical removal of cataracts have made treatment very effective. Three major topics related to aging and the eye that will be discussed here are presbyopia, age-related macular degeneration and senile cataract.
Keywords: Age-related macular degeneration; Aging; Cataract; Eye; Presbyopia